Heterosis for Yield and Yield Components in Wheat (Triticum aestevum L.) Under Saline and Normal Environments - Dubey, L K; Sastry, E V D; Singh, Kishenjit (Annals of Arid Zone, 2016)
Thirty six hybrids, evolved from nine genetically diverse genotypes, were evaluated under normal and saline environments along with parental lines to determine the nature and extent of heterosis for eight characters, including grain yield per plant. The crosses Raj 3077 x Kharchia 65, Raj 3765 x Raj 3880, Job 666 x Kharchia 65, Job 666 x Raj 3880 and Kharchia 65 x Raj 3880 exhibited desirable heterobeltiosis under normal condition. Out of these, Job 666 x Kharchia 65, Job 666 x Raj 3880 and Kharchia 65 x Raj 3880 also exhibited desirable heterobeltiosis for grain yield under salinity. The heterotic crosses for yield were found to be heterotic for 1000-grain weight and harvest index. Thus, heterosis for these two characters has influenced the heterosis in yield. The heterosis for grain yield per plant of superior crosses in saline condition was mainly contributed by number of productive tillers and harvest index.